Lipid droplet-associated PAT-proteins show frequent and differential expression in neoplastic steatogenesis - Straub, Beate Katharina; Herpel, Esther; Singer, Stephan; Zimbelmann, Ralf; Breuhahn, Kai; Macher-Göppinger, Stephan; Warth, Arne; Lehmann-Koch, Judith; Longerich, Thomas; Heid, Hans; Schirmacher, Peter (Modern pathology, 2010)
In many human cancers, lipogenic pathways are activated; in some tumors, such as hepatocellular carcinoma, this is reflected by the presence of visible lipid droplets. Yet, the biology of steatogenesis in malignant tumors is largely unknown. We have recently shown that lipid droplet-associated proteins of the PAT-family, named after their constituents perilipin (perilipin 1), adipophilin (perilipin 2), and TIP47 (perilipin 3) are differentially expressed in hepatic steatogenesis. We have comprehensively investigated PAT-expression in neoplastic steatogenesis as well as in respective normal tissues with immunohistology and electron microscopy as well as protein biochemical and molecular biological methods. By staining for PAT-proteins, we found lipid droplet accumulation to be a frequent phenomenon of carcinoma cells. Although adipophilin and TIP47 stained almost ubiquitously the rim of lipid droplets in various tumor types, especially those with clear cell phenotype, perilipin was restricted to lipid droplets of hepatocellular adenoma and carcinoma, sebaceous adenoma and carcinoma, and lipomatous tumors. In hepatocellular carcinoma, perilipin, adipophilin, and TIP47 were coexpressed, and showed regional heterogeneity with a predominantly mutually exclusive localization pattern. In step-wise carcinogenesis, adipophilin expression correlated with the proliferation rate and was upregulated during early tumorigenesis, whereas perilipin was often lost during hepatocarcinogenesis. In conclusion, expression analysis of PAT-proteins showed that by far more carcinomas contain (PAT-positive) lipid droplets than expected by conventional light microscopy. PAT-proteins, such as perilipin, are differentially expressed in different tumor types and thus may support diagnostic considerations. Because inhibition of lipogenesis has been shown to exert antineoplastic effects, PAT-proteins may represent targets for interventive strategies.
Gesehen am 01.09.2023